Structure and properties of Mg, Al, Ti oxide and nitride layers formed by ion-plasma sputtering - Pidkova, V.; Brodnikovska, I.; Duriagina, Z.; Petrovskyy, V. (Functional Materials, 2014)
Dielectric layers of Al₂O₃, MgO, AlN and TiO₂ were formed by using ion-plasma sputtering method. Their microstructure and electrophysical properties in the range of 20 - 400°C were investigated. The conductivity mechanism, depth of traps and losses mechanism were established. The ohmic contact formation was revealed in TiO₂/40X13 system through which an injection of charge carries from the alloy into the dielectric layer occurs and its contribution to the electric equivalent circuit of substitution was assessed.